1990
DOI: 10.1139/f90-260
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Potentially Harmful Phytoplankton Species in the Northern Strait of Georgia, British Columbia

Abstract: Spatial and temporal distributions of Chaetoceros convolutum (including C. concavicorne), Heterosigma akashiwo, Protogonyaulax (= Alexandrium) catenella, and Dinophysis are presented for the northern Strait of Georgia from March to September, 1986. In spring C. convolutum was found on the slightly stratified eastern side in concentrations just below those leading to kills of caged salmon (4-5000 cells∙L−1). The northern Strait became thermally stratified in summer. At this time the population centre of C. conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
4
10
0
Order By: Relevance
“…It should be pointed out that Lee et al (1989) reported the presence of both OA and DTX-1 in a sample of Dinophysis norvegica, while another sample of this species collected from Norway during the same month contained only DTX-1. There were other instances (Haamer et al 1990) in which DSP toxins were apparently low in the samples containing high proportions of D. norvegica in excess of the critical concentration (200 cells I-') for DSP (Haigh & Taylor 1990). This was also true in our samples.…”
Section: Discussionsupporting
confidence: 68%
“…It should be pointed out that Lee et al (1989) reported the presence of both OA and DTX-1 in a sample of Dinophysis norvegica, while another sample of this species collected from Norway during the same month contained only DTX-1. There were other instances (Haamer et al 1990) in which DSP toxins were apparently low in the samples containing high proportions of D. norvegica in excess of the critical concentration (200 cells I-') for DSP (Haigh & Taylor 1990). This was also true in our samples.…”
Section: Discussionsupporting
confidence: 68%
“…The photosynthetic dominant in June was Heterosigma akashiwo, which was abundant throughout the Strait at all depths sampled (Haigh and Taylor 1990). Highest abundance in the northwest suggests that growth of H. akashiwo was enhanced by the nutrient pump effect of the plume and/or that it was injected from the northern passages.…”
Section: Grazing Pressurementioning
confidence: 96%
“…Diatoms are often implicated in such events (Bell, 1961;Taylor et al 1985;Farrington, 1988;Rensel, 1993;Kent et al 1995;Tester and Mahoney, 1995). The raphidophyte Heterosigma akashiwo presents a serious problem for aquaculture in many parts of the world including Japan, North America, Asia and New Zealand (Haigh and Taylor, 1990;Change et al 1990;Black et al 1991;Mackenzie, 1991;Qi et al 1993;Honjo, 1994). Affected salmon shows signs of gill and intestinal pathology and death has been attributed to impairment of the gills' respiratory and osmoregulatory functions (Change et al 1990).…”
Section: Other Types Of Toxic Bloommentioning
confidence: 99%